2002
DOI: 10.1111/j.1095-8649.2002.tb00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Predation on Atlantic salmon and sea trout during their first days as postsmolts

Abstract: Radio-tagged smolts of Atlantic salmon Salmo salar and sea trout Salmo trutta were predated heavily by sea birds after crossing the saline limit in the estuary of the River Skjern, Denmark. Most predation took place within the first 9 h after estuarine entry. The field data do not contradict the hypothesis of maladaptive anti-predatory behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 21 publications
1
55
0
1
Order By: Relevance
“…In the inner estuary, high concentrations of smolt predators may account for the extreme size-selected survival. Predators have been reported to favour the area around head-of-tide or at constriction points within estuaries during the smolt run (Hvidsten and Lund 1988;Dieperink et al 2002;Jepsen et al 2006). Salmon are first exposed to salt water in the inner estuary and mortality may occur as a result of osmotic stress or an associated reduction in predator avoidance ability (Järvi 1989;Handeland et al 1996).…”
Section: Influence Of Body Size On Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…In the inner estuary, high concentrations of smolt predators may account for the extreme size-selected survival. Predators have been reported to favour the area around head-of-tide or at constriction points within estuaries during the smolt run (Hvidsten and Lund 1988;Dieperink et al 2002;Jepsen et al 2006). Salmon are first exposed to salt water in the inner estuary and mortality may occur as a result of osmotic stress or an associated reduction in predator avoidance ability (Järvi 1989;Handeland et al 1996).…”
Section: Influence Of Body Size On Survivalmentioning
confidence: 99%
“…Using acoustic telemetry, researchers have estimated mortality rates during the estuarine migration, which is the transition point from riverine to marine habitats, the place the fish spend their first few weeks in the ocean, and a place and time where previous studies have reported intense mortality (Kocik et al 2009;Davidsen et al 2009;Halfyard et al 2012). Causes of estuarine losses may include predation (e.g., Hvidsten and Møkkelgjerd 1987;Hvidsten and Lund 1988;Dieperink et al 2002), osmotic stress (Staurnes et al 1996;McCormick et al 1998), and (or) their interaction (Järvi 1989;Handeland et al 1996).…”
Section: Introductionmentioning
confidence: 98%
“…There is increasing concern that greater rates of marine mortality documented among Atlantic salmon over the past decade may be largely incurred in the near-shore coastal zone, where smolt may be exposed for the first time to a large field of predators (Blackwell & Juanes 1998, Dieperink et al 2002. It is thus imperative to understand the mechanisms employed by Atlantic salmon during this early stage in the marine migration and the influence of environmental factors on migratory patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that post-smolts are exposed to high predation immediately after sea entry (Reitan et al 1987;Hvidsten and Lund 1988;Dieperink et al 2002) and that the risk of predation increases if fish suffers from osmotic stress (Järvi 1989;Handeland et al 1996;Kennedy et al 2007). It may therefore be suggested that the extended residency of the first smolt group in the lower part of the river was related to their low gill Na + , K + -ATPase activity and a need to improve seawater tolerance before entering seawater.…”
mentioning
confidence: 99%